Overview of Loss and Waste - Robertson, Kai (2018)
The presentation Overview of Loss and Waste is by Kai Robertson, lead advisor for the FLW Protocol at the World Research Institute. Presented at the WBCSD Climate Smart Agriculture workshop at the University of Vermont, Burlington, VT on 28 March 2018.